Pengaruh Kualitas Produk dan Promosi Terhadap Keputusan Pembelian The Pucuk Harum pada Mahasiswa FEB Angkatan 2022 Universitas Muhammadiyah Bandung - Pirdaus, Muhamad; Zahrah, Halimah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to examine the effect of product quality and promotion on purchasing decisions of The Pucuk Harum among students of the Faculty of Economics and Business, Class of 2022, Universitas Muhammadiyah Bandung. This research employs a quantitative approach using a survey method. The data were collected through questionnaires distributed to respondents and analyzed using multiple linear regression analysis. The results show that product quality has a positive and significant effect on purchasing decisions. Promotion also has a positive and significant effect on purchasing decisions. Simultaneously, product quality and promotion significantly influence purchasing decisions of The Pucuk Harum. These findings indicate that improving product quality and implementing effective promotional strategies play an important role in encouraging consumers’ purchasing decisions.